Two cases of foreign body in the paranasal sinus with fungal infection - HATANO, Takashi; ORIDATE, Nobuhiko; SHIONO, Osamu; NINOMIYA, Hiroaki; NISHIMURA, Goshi; TANIGAKI, Yuji (jibi to rinsho, 2022)
Paranasal sinus foreign bodies occur less frequently than nasal foreign bodies. In recent years, the number of such cases that are induced in the clinical setting have increased with the development of dental treatments. We herein report two cases of foreign bodies in the sinus that were accompanied by fungal infection. The manifestations of paranasal foreign bodies range from asymptomatic presentations, to immediate or delayed sinusitis symptoms. Surgical removal of the foreign body is indicated even in asymptomatic cases because coexisting fungal infection may be present. Although less invasive endoscopic sinus surgery has been increasingly used in recent years, it is desirable to adopt an appropriate procedure according to the size and location of the foreign body.